2022
DOI: 10.1038/s41598-022-11045-7
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics of lung tissue reveals differences in inflammation and alveolar-capillary barrier response between atelectasis and aerated regions

Abstract: Atelectasis is a frequent clinical condition, yet knowledge is limited and controversial on its biological contribution towards lung injury. We assessed the regional proteomics of atelectatic versus normally-aerated lung tissue to test the hypothesis that immune and alveolar-capillary barrier functions are compromised by purely atelectasis and dysregulated by additional systemic inflammation (lipopolysaccharide, LPS). Without LPS, 130 proteins were differentially abundant in atelectasis versus aerated lung, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
0
1
0
Order By: Relevance
“…Evaluating the effect of atelectasis on proteomics is fundamental to understanding the biological alterations generated by ARDS. Rashid et al [98] studied proteomics following a model of acute lung damage generated with lipopolysaccharide (LPS) and endotoxin. They were able to reflect how atelectasis in these cases has a clear effect on increasing inflammation and dysfunction of the alveolar-capillary membrane.…”
Section: Prone Positioning and Biomarkers In Covid-19 And Non-covid-1...mentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluating the effect of atelectasis on proteomics is fundamental to understanding the biological alterations generated by ARDS. Rashid et al [98] studied proteomics following a model of acute lung damage generated with lipopolysaccharide (LPS) and endotoxin. They were able to reflect how atelectasis in these cases has a clear effect on increasing inflammation and dysfunction of the alveolar-capillary membrane.…”
Section: Prone Positioning and Biomarkers In Covid-19 And Non-covid-1...mentioning
confidence: 99%
“…As markers of alveolar-capillary dysfunction, they found extracellular matrix glycoproteins, vascular endothelial growth factor, and fibrinogen independently of the presence of systemic endotoxemia. Additionally, Endotoxemia promoted further metabolic changes in atelectasis with increased glycolytic enzymes, carbon metabolism, and glycolysis pathways [98].…”
Section: Prone Positioning and Biomarkers In Covid-19 And Non-covid-1...mentioning
confidence: 99%
“…In a recent large animal study, proteomics of lung tissue revealed differences in inflammation and alveolar‑capillary barrier response between atelectasis and aerated regions. Atelectasis regions showed a predominance of negative enrichment related to the extracellular matrix, immune response, tissue development, stress, and metabolism [ 168 ]. In a mice model, Yue et al [ 169 ] observed that the proteomic profile differs between direct lipopolysaccharide-induced lung injury and indirect lung injury.…”
Section: Omics In Ards Researchmentioning
confidence: 99%